An investigation of coaches' awareness of injury in elite adolescent rugby union in Northern Irish schools - A qualitative study. (September 2022) - Anderson, David; Cathcart, John; Kerr, Daniel; Moore, Isabel; Hislop, Mike; Wilson, Iseult
Abstract: Objectives: To examine the decision-making processes employed by schools' Rugby coaches in the management of injured players and to explore the factors that influenced those decisions. A secondary objective was to gauge interest in an education focused toolkit for schools' Rugby coaches. Design: A qualitative study using one-to-one online interviews. Setting: Schools who compete in the Ulster Schools' Cup Rugby competition. Participants: Eleven Rugby union coaches from four post primary schools. Outcome measures: A thematic analysis approach was used to examine the factors that influence schools' Rugby coaches' decision-making processes in the management of injured players. Results: Findings suggest coaches are influenced in their decision making by four primary factors: their experience and learning, their relationships with other stakeholders, their knowledge and understanding of the roles and responsibilities of medical staff, healthcare and health fitness professionals, and resources available to them. Conclusions: Schools' Rugby coaches play a significant role in the supervision of injured adolescent Rugby players, often drawing from their playing and coaching experiences. Schools retain, or recommend the services, of healthcare professionals (HCPs) and health and fitness professionals (HFPs). The role of these healthcare and health and fitness professionals, along with their qualifications and experience is not fully understood by coaches. Coaches acknowledge that there is a need for further training and would welcome education initiatives aimed at increasing awareness of musculoskeletal injury in schoolboy Rugby players. Highlights: Schools' Rugby coaches play a significant role in the management of injured schoolboy Rugby players. Coaches often rely on their own playing and coaching experience; as experience will vary from coach to coach, so too will advice and guidance given to injured players. Players are often relied upon to advise the coach on their readiness to return to play. It is not evident that supervised, formal return to play programmes are commonly used in schoolboy Rugby. There is a need for a greater awareness of musculoskeletal injury in schoolboy Rugby.